(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, we will dwell on the legal system of Avesta, which has a unique place in the history of our ancient country, as well as on the issues of proper living of the family, a small part of society. .